Pemahaman Strategi Komunikasi pada Ranah Cross Culture Indonesia dan Jepang sebagai Bentuk Peningkatan Hospitality di Yan Yan Silver - Andriyani, Anak Agung Ayu Dian; Sudipa, Made Henra Dwikarmawan; Tarasista, Ni Putu Vineisya (Indra Institute Research & Publication, 2025)
Bali Island, as a tourism destination grounded in the concept of local wisdom that underpins social harmony, continues to exist and develop innovative approaches to sustainable tourism. This concept emphasizes tourism development that does not harm the environment or culture while providing economic benefits, protecting the environment, and preserving local socio-cultural values. One of the key attractions supporting this concept is the empowerment of micro, small, and medium enterprises (UMKM) to strengthen the local economy, including Yan Yan Silver. Based on a situational analysis conducted through direct observation and interviews, this community service program aims to enhance the cross-cultural communication competence of workers at Yan Yan Silver, a silver craft in Bali that frequently interacts with Japanese tourists. Limited understanding of Japanese cultural values, politeness strategies, and effective communication techniques has led to miscommunication and a decline in service quality. Therefore, this program focuses on practical training in Japanese-language communication strategies, the introduction of Japanese interaction norms, and culturally based hospitality practices. The methods employed include preliminary observation, interviews, participatory training, role-play simulations, and evaluation. The evaluation results before and after the training clearly indicate a significant improvement in workers readiness to interact with Japanese tourists, particularly in the use of polite expressions, appropriate body language, and an enhanced understanding of Japanese tourists communication expectations. This training is expected to contribute to improving service quality and strengthening the competitiveness of Yan Yan Silver as a culturally based silver gallery destination.